Metabolic Fingerprinting of In-bag Dry- and Wet-aged Lamb With Rapid Evaporative Ionisation Mass Spectroscopy - Zhang, R; Ross, AB; Yoo, MJY; Farouk, MM (Elsevier BV, 2021)
The effect of in-bag dry- and wet-ageing on metabolite profiles of lamb legs was determined using Rapid Evaporative Ionisation Mass Spectrometry (REIMS). Using orthogonal projection to latent structures-discriminant analysis (OPLS-DA) with REIMS, 1705 metabolite ions were identified (Q2 = 0.86) in four muscles: m. semimembranosus, m. biceps femoris, m. vastus lateralis and m. rectus femoris. A total of 663 metabolites differed between ageing methods (P < 0.05) which mainly resulted from proteolysis and lipid metabolism. Dry-aged lamb had higher pH (P = 0.016) and lower moisture content (P = 0.034) than the wet-aged. Dry-ageing produced more (P < 0.05) smaller sized metabolites including dipeptides and free amino acids and lipid oxidation metabolites compared to wet-aged equivalents. Different muscles had distinct REIMS metabolic profiles. Outcomes of this study demonstrated that REIMS can be used for authentication between in-bag dry- and wet-aged lamb based on their metabolic fingerprints.
Keywords: Meat ageing; In-bag dry-aged lamb; REIMS; Metabolic fingerprinting; Dipeptides